CORNELIA DE LANGE SYNDROME WITH SEPSIS NEONATORUM AND RESPIRATORY DISTRESS SYNDROME - Angga Nugraha (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Pterygium is a disorder of the conjunctiva bulbi, fibrovaskular growth conjunctival degenerative and invasive that marked with eye irritating, itchy, redness, foreign body sensation, and may cause astigmatism or obstruction of the visual axis that will impair vision. The cause of pterygium is still not known. Some risk factors for pterygium include ultraviolet exposure, chronic micro trauma to the eye, and microbial or viral infection. Female, 50 years old, came with eye complaint of foreign body sensation since 3 years ago. Complaint followed with redness eyes and sore if exposed to wind. On physical examination found good general condition, compos mentis, blood pressure was 120/80 mmHg, pulse 80 x/min, respiration 16 x/min, temperature was 36.6 oC. At the ophthalmologicalexamination found reddish white membrane around the nasal and triangular apex passing the limbus and the edge of the pupil. Patients diagnosed as pterygium oculi dextra stage III. The management was education to patient in order to protect the eyes from sunlight, dust, and wind, and operative procedure to remove the pterygium. The prognosis to this patient is good. [J Agromed Unila 2015; 2(1):18-22]Keywords: antibiotic, oculi dextra, pterygium, woman